Analisis Penyebab Kurang Bayarnya Gaji Karyawan Bagian Perawatan di Perkebunan Kelapa Sawit dengan Deming’s View Process System, Prinsip 5W+1H dan Five Whys Analysis - M Hudori (JURNAL CITRA WIDYA EDUKASI, 2018)
Inadequate salary payments such as underpaid employee salaries will result in decreased employee productivity, including maintenance employee in the palm oil plantation. The problem can not be solved carefully if not analyzed the root cause. The purpose of this research is to determine the root causes of the problem of underpaid maintenance employee salaries in the palm oil plantation and the solution. The research was conducted on February 20th –May 27th, 2017 at a palm oil plantation company in East Kalimantan Province. Data analysis was done with Deming's View Process System concept, the 5W + 1H (What, Who, Where, When, Why & How) principles and Five Whys Analysis to search for the root cause of the problem. The result show that the root causes of the problem are: 1) no socialization of the type of maintenance work required in the palm oil plantation; and 2) the field supervisor has less supervision on the work of the foreman. The solutions are socialize to the maintenance foremans on the types of maintenance work required in the palm oil plantation and supervise their work, especially on the aspect of maintenance administration.